Exercise effects on cognitive functioning in young adults with first-episode psychosis: FitForLife. Issue 3 (6th May 2018) - Hallgren, Mats; Skott, Maria; Ekblom, Örjan; Firth, Joseph; Schembri, Adrian; Forsell, Yvonne
Abstract: Background: Exercise has mood-enhancing effects and can improve cognitive functioning, but the effects in first-episode psychosis (FEP) remain understudied. We examined the feasibility and cognitive effects of exercise in FEP. Method: Multi-center, open-label intervention study. Ninety-one outpatients with FEP (mean age = 30 years, 65% male) received usual care plus a 12-week supervised circuit-training program, consisting of high-volume resistance exercises, aerobic training, and stretching. Primary study outcome was cognitive functioning assessed by Cogstate Brief Battery (processing speed, attention, visual learning, working memory) and Trailmaking A and B tasks (visual attention and task shifting). Within-group changes in cognition were assessed using paired sample t tests with effect sizes (Hedges' g ) reported for significant values. Relationships between exercise frequency and cognitive improvement were assessed using analysis of covariance. Moderating effects of gender were explored with stratified analyses. Results: Participants exercised on average 13.5 (s .d . = 11.7) times. Forty-eight percent completed 12 or more sessions. Significant post-intervention improvements were seen for processing speed, visual learning, and visual attention; all with moderate effect sizes ( g = 0.47–0.49, p < 0.05). Exercise participation was also associated with a positive non-significant trend for working memory ( p < 0.07). Stratified analyses indicated a moderating effect of gender. Positive changes were seen among females only for processing speed, visual learning, working memory, and visual attention ( g = 0.43–0.69). A significant bivariate correlation was found between total training frequency and improvements in visual attention among males ( r = 0.40, p < 0.05). Conclusion: Supported physical exercise is a feasible and safe adjunct treatment for FEP with potential cognitive benefits, especially among females.